GABAA Receptor β2E155 Residue Located at the Agonist-Binding Site Is Involved in the Receptor Gating - Jatczak-Śliwa, Magdalena; Kisiel, Magdalena; Czyzewska, Marta Magdalena; Brodzki, Marek; Mozrzymas, Jerzy Władysław (Frontiers in Cellular Neuroscience, 2020)
GABAA receptors play a crucial role in mediating inhibition in the adult brain. In spite of progress in describing (mainly) the static structures of this receptor, the molecular mechanisms underlying its activation remain unclear. It is known that in the α1β2γ2L receptors, the mutation of the β2E155 residue, at the orthosteric binding site, strongly impairs the receptor activation but the molecular and kinetic mechanisms of this effect remain elusive. Herein, we investigated the impact of the β2E155C mutation on binding and gating of the α1β2γ2L receptor. To this end, we combined the macroscopic and single-channel analysis, the use of different agonists (GABA and muscimol - MSC) and flurazepam (FLU) as a modulator. As expected, the β2E155C mutation caused a vast right-shift of the dose-response (for GABA and MSC) and, additionally, dramatic changes in the time course of current responses, indicative of alterations in gating. Mutated receptors showed reduced maximum open probability and enhanced receptor spontaneous activity. Model simulations for macroscopic currents revealed that the primary effect of the mutation was the downregulation of the preactivation (flipping) rate. Experiments with MSC and FLU further confirmed a reduction of the preactivation rate. Our single-channel analysis revealed the mutation impact mainly on the second time component in the shut times distributions. Based on model simulations, this finding further confirms that this mutation affects mostly the preactivation transition, supporting thus the macroscopic data. Altogether, we provide new evidence that the β2E155 residue is involved both in binding and gating (primarily preactivation).